Audiovisual accessibility and translation in cinema and theatre: from paper to practice - Enríquez-Aranda, Mercedes; Varela-Salinas, María José (My University, 2019)
In the last decade, very specific regulations have been developed in Spain regarding accessibility to the media. With a pioneering character, in 2010 a general law of audiovisual communication was published that aims to guarantee the rights of access to audiovisual communication by people with visual or hearing disabilities. In 2013, a royal decree act disseminated specific terminology of the field (universal accessibility and design) as well as express indications on its implementation (reasonable adjustments and scope of application). Government Centers (Spanish Center of Subtitling for the Deaf and Audiodescription) and academic initiatives (2016) serve, on the one hand, to "promote accessibility in the audiovisual media environment through subtitling and audio description services" (CESyA, 2018: online) and, on the other hand, to introduce the teaching and the learning of the most demanded accessible practices. The theoretical pillars for the implementation of accessible practices in audiovisual media are built in Spain. It is time to analyse if the real practices correspond to the theoretical demands. This paper presents the results derived from the study of audiovisual accessibility and translation in cinema and theatre in the city of Malaga (Spain), Mediterranean paradigm of a multilingual cultural offer (fifth cultural capital in Spain in 2018). We study the accessible practices (subtitling for the deaf, audio description, surtitling, respeaking, sign language interpreting), the technical means (digital convergence), the languages involved (intra and interlinguistic translation) and the role of the professionals (producers and translators) in the process. The interpretation of these data suggests improvements in favour of the social inclusion of all recipients. • CESyA (2018) (https://www.cesya.es/drupal7/quienes). • Talaván, N., J. J. Ávila-Cabrera & T. Costal (2016): Traducción y accesibilidad audiovisual, Barcelona: UOC .
Keywords: Traducción; Audiovisual accessibility; Audiovisual translation; Cinema; Theatre; Accesibilidad